Cloning, expression and characterization of bacterial L - glutaminase - Taher Talal Mahrous Ahmed; Mohamed G. Farahat; Zienat Kamel Mohamed Ibrahim (Cairo : Taher Talal Mahrous Ahmed, 2021)
L-Glutaminase has received an increased importance in recent years for its anti-carcinogenic potential. In this study, Klebsiella michiganensis was isolated from the Lake Mariout and the glsA gene encoding L-glutaminase from was cloned into pQE-80L expression vector and expressed in E. coli BL21.The recombinant histidine-tagged L-glutaminasewas purified to homogeneity by Ni{u2013}NTAaffinity chromatography and displayed a single 33.0 kDa band on SDS-PAGE.The purified functional enzyme exhibited a specific activity at 89 U/mg and inhibited the growth of human colon cancer cells (HCT116) with IC50 value of 2.4±0.7 U/ml
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany - Microbiology
Issued also as CD
Keywords: L-Glutaminase; Cloning; Screening